The Impact of Democracy on Economic Growth in sub-Saharan Africa - Barreto, Montserrat Lleyda (Department of Political Studies, 2014)
This research will deal with regime dynamics (early interruption of democracies, early maintaining of democracies, late interruption of democracies, late maintaining of democracies, maintaining autocracies, and liberalizing autocracies), levels of democracy (liberal democracy, electoral democracy, and hybrid regimes) and their relationship with economic growth. Regime dynamics refers to the stability or interruption of democratic and authoritarian regime. The meaning of the regime dynamics categories are: maintaining autocracies (countries that have maintained their authoritarian regime over time), liberalizing autocracies (countries that are not considered close autocracies, having some democratic aspects, such as their electoral system with a set of minimal civil rights and freedom), late interruption democracies (countries that became democracies after 1997 but broke down), late maintaining democracies (countries that became democracies after 1997 and have maintained their democratic status), early interruption democracies (countries that became democracies before 1997 but broke down), early democratizers maintaining (countries that became democracies before 1997 and have maintained their democratic status). These categories are created based on how these countries score in the Freedom House. A total of 47 sub-Saharan African countries will be researched over time, from 1988 until 2008, in order to verify whether countries are included in which group of the regime dynamics' typologies. The variable of economic growth is affected by the regime dynamics. In this case, early maintaining democracy is positive correlated with economic growth. The maintenance of regime, being it a democracy or an autocracy has higher growth rates compared to countries that have democratic or autocratic interruptions. Therefore, regime stability over time is a key variable in order to understand economic growth in sub-Saharan Africa. The impact of regime dynamics and levels of democracy on economic growth has been tested by applying Time Series Analysis (statistical methodology) and Ordinary Least Square method.